(untitled) (Lumen Veritatis: Jurnal Filsafat dan Teologi, 2025)
This article aims to criticize the act of glorifying sexism on women’s bodies in the world of social media content from the perspective of John Paul II’s theology of the body. This scientific study employs descriptive qualitative methods and basic data collection techniques, such as in-depth observation and literature review. The data analysis technique follows the steps outlined by Miles and Huberman, namely data reduction, data display, and drawing conclusions. Based on the results of the analysis, it can be concluded that 1) content media has a significant effect on the act of glorifying wommen’s bodies. 2) Women tend to show their bodies transparently in the world of social media content for the sake of self-glorification. 3) the act of glorifying on women’s bodies is a from of harassment of the body as a representation of God, and, 4) the concept of Jhon Paul II theology of the body plays a significant role in reawakening all humans, especially women, to respect, appreciate and uphold the dignity and significance of their bodies as an image and representation of God in the world.